2014
DOI: 10.5194/acp-14-505-2014
|View full text |Cite
|
Sign up to set email alerts
|

Long-range transport of giant particles in Asian dust identified by physical, mineralogical, and meteorological analysis

Abstract: Abstract. Giant particles transported over long distances are generally of limited concern in atmospheric studies due to their low number concentrations in mineral dust and possible local origin. However, they can play an important role in regional circulation of earth materials due to their enormous volume concentration. Asian dust laden with giant particles was observed in Korea on 31 March 2012, after a migration of about 2000 km across the Yellow Sea from the Gobi Desert. Scanning electron microscopy (SEM)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 47 publications
2
69
1
1
Order By: Relevance
“…However, there is evidence of Aeolian dust transport and sedimentation of giant dust particles in the ocean up to 10 000 km away from source regions in the tropical Atlantic (Prospero et al, 1970;Carder et al, 1986) and Pacific (e.g. Betzer et al, 1988;Middleton et al, 2001;Jeong et al, 2014). Airborne observations also confirmed that the coarsest particles (> 20 µm in diameter) are far from completely depleted over the North Atlantic (McConnell et al, 2008;Ryder et al, 2013).…”
Section: Introductionsupporting
confidence: 51%
“…However, there is evidence of Aeolian dust transport and sedimentation of giant dust particles in the ocean up to 10 000 km away from source regions in the tropical Atlantic (Prospero et al, 1970;Carder et al, 1986) and Pacific (e.g. Betzer et al, 1988;Middleton et al, 2001;Jeong et al, 2014). Airborne observations also confirmed that the coarsest particles (> 20 µm in diameter) are far from completely depleted over the North Atlantic (McConnell et al, 2008;Ryder et al, 2013).…”
Section: Introductionsupporting
confidence: 51%
“…Nevertheless, in this version of CHIMERE the formation of coarse nitrate due to the reaction of calcium with nitric acid (issued from the anthropogenic pollution) is not considered and could enhance the interactions between natural and anthropogenic emissions as it has been studied in China [101]. The transport of "giant" mineral particles, which can be defined as particles with diameters exceeding 10 µm, is rarely documented in the literature according to a recent study [102]. This study analyzes a specific Asian episode leading to the delivery of big particles in Korea thanks to mid-tropospheric strong winds.…”
Section: Particle Size Distributionmentioning
confidence: 99%
“…Asian dust in Mt. Tateyama (central Japan) snow samples show a median volume diameter 6-21 μm (Osada et al, 2004), while dust particles of up to 60 μm (equivalent sphere diameter) have been transported as far as 2000 km away (Jeong et al, 2013). Therefore, transport of large particles from the remote arid region to the high-alpine glacier surface on the Tibetan Plateau is feasible.…”
Section: Composition Discrepancy Between Snow Dust and Cryoconitementioning
confidence: 99%